Implementasi Program Literasi dalam Meningkatkan Kemampuan Bahasa Anak Speech Delay - Niarti, Sriyan Kumala; Sundari, Iis; Paramitha, Paramitha; Erni, Erni; Fitriani, Hilda; Izza, Hillia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Speech delay is a serious condition that can impede a child's language and communication development, which significantly impacts their future life and educational prospects. This study aims to descriptively review and elaborate on the implementation of a literacy program as an intervention to improve the language ability of children with speech delay in a [e.g., Kindergarten/School] setting. The research method used is descriptive qualitative, with research subjects including [e.g., the principal, classroom teachers, and children with speech delay]. Data collection techniques involved observation, interviews, and documentation. The results indicate that the implementation of the literacy program, conducted through habituation, development, and structured learning, successfully improved the language ability of children with speech delay, particularly in terms of vocabulary expansion, clarity of pronunciation, and verbal interaction. The program emphasized the use of engaging visual media, such as picture storybooks, to facilitate receptive language comprehension before transitioning to expressive language.